2023
DOI: 10.3892/ijo.2023.5502
|View full text |Cite
|
Sign up to set email alerts
|

BST2 regulated by the transcription factor STAT1 can promote metastasis, invasion and proliferation of oral squamous cell carcinoma via the AKT/ERK1/2 signaling pathway

Abstract: Oral squamous cell carcinoma (OSCC) is one of the main types of head and neck squamous cell carcinoma. Although progress has been made in treating OSCC, it remains a threat to human health, and novel therapeutic strategies are needed to extend the lifespan of patients with OSCC. The present study, evaluated whether bone marrow stromal antigen 2 (BST2) and STAT1 were potential therapeutic targets in OSCC. Small interfering RNA (siRNA) or overexpression plasmids were used to regulate BST2 or STAT1 expression. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…FEN1 may directly or indirectly regulate HLA-DR and PD-L1 in OSCC via the IFN-γ/JAK/STAT1 pathway ( Wang et al, 2023 ). Shan et al reported that the downregulation of STAT1/BST2 axis inhibited OSCC cell growth through the AKT/ERK1/2 signaling pathway ( Shan et al, 2023 ). Overall, above results demonstrate that the JAK/STAT signaling pathway is a potential molecular target and biomarker for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…FEN1 may directly or indirectly regulate HLA-DR and PD-L1 in OSCC via the IFN-γ/JAK/STAT1 pathway ( Wang et al, 2023 ). Shan et al reported that the downregulation of STAT1/BST2 axis inhibited OSCC cell growth through the AKT/ERK1/2 signaling pathway ( Shan et al, 2023 ). Overall, above results demonstrate that the JAK/STAT signaling pathway is a potential molecular target and biomarker for OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that CENPU was a key gene in the development of LUAD, closely associated with the infiltration of various immune cells ( Zhou et al, 2021 ). Shan et al found that BST2 contributes to the promotion of metastasis, invasion and proliferation of oral squamous cell carcinoma ( Shan et al, 2023 ). Through the above core gene-associated lncRNAs, it has been shown that the above lncRNAs were related to the value-added and differentiation regulation of cancer cells, and LINC00174 is related to immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the impact on mRNA metabolism, IL-17 is able to perform its activity synergistically with other cytokines and activates diverse signaling pathways. Interleukin-17 and TNF-α synergistically activate NF-κB, a transcriptional factor with known roles in the promotion of inflammation and OSCC progression [ 117 , 118 , 119 ]. Interleukin-17 signals cooperatively with the IFN-γ enhances activation of STAT1, a molecule involved in signaling pathways important for OSCC growth and metastasis [ 120 , 121 ].…”
Section: Il-17 Dependent Inflammation and Osccmentioning
confidence: 99%